A CROSS-SECTIONAL STUDY TO FIND OUT THE SIGNIFICANT PREVALENCE OF CHRONIC KIDNEY DISEASE IN TYPE 2 DIABETICS IN EASTERN INDIA - SANDIP KUMAR KUNDU; SIBAPRAKASH MUKHERJEE; SHUBHRANGSU SAMANTA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Diabetes mellitus (DM) is a metabolic syndrome clinically presenting hyperglycemia with underlying absolute or relative insulin deficiency. Type 2 DM (T2DM) presently comprises about 90% of the diabetic population of the World. Diabetes leads to many complications. One major complication of long-term poorly controlled diabetes is diabetic nephropathy which usually leads to end-stage renal disease (ESRD). There are mainly two crucial markers to assess renal impairment– (1) Glomerular filtration rate (GFR) and (2) Microalbuminuria. The objective of our study is to find out the prevalence of chronic kidney disease (CKD) in T2DM patients. Methods: We measured glycated hemoglobin (HbA1c), serum creatinine, urinary ACR, and estimated GFR (eGFR) (by Modification of Diet in Renal Disease formula) in selected 105 T2DM patients aged 40–70 years (mean duration of diabetes is 10.01±3.46 years). We analyzed the data by appropriate statistical software and assessed the prevalence of CKD (with Urinary ACR and eGFR) in T2DM patients (with fasting blood glucose, 2-h OGTT, and HbA1c). Results: This study shows that 30 out of 105 diabetic patients were suffering from CKD, with a prevalence of 28.57%. Discussion: In our study; out of 105 T2DM patients, 30 (28.57%) patients had some stages of CKD. Nineteen (63.33%) out of these 30 CKD patients had albuminuria (both micro and macroalbuminuria), and 11 (36.67%) out of 30 CKD patients had normoalbuminuria (ACR <30 mg/g). Conclusion: There is a high prevalence (28.57%) of CKD in T2DM patients, and early detection and treatment of diabetic nephropathy, along with tight glycemic control, helps prevent ESRD.